Readiness of digital technology adoption in the Malaysian construction project management - Ong, Jiun Ren (2020)
Emerging technologies are changing the way people work and live. A new digital world has coexisted with the physical world as a result of creative disruption by the emerging technologies. These digital technologies impact all kinds of businesses and it will have no exception to the construction industry. McKinsey Global Institutes industry digitisation index 2015 shows that construction industry is the second least digitalised sectors among the 22 sectors studied. This research explores the adoption of digital technology by the Malaysian construction industrial practitioners, assess the awareness of construction practitioners towards digital adoption and analyse the preparedness in digital technology adoption. A theoretical framework was synthesised after the literature related to the application, current technology adoption and lesson learnt in digitalisation in the construction industry has been reviewed. A questionnaire encompassed the theoretical framework were used as research instrument to collect the raw data from the industry. Based on the 122 responses from the questionnaire survey, this research found that the Malaysian construction industry adopted digital technology mainly used for real time communication. However, they are yet to unleash the potentials of digital technologies such as data analytics and data representation. It has also revealed that the younger generation are more willing to adopt new digital technologies Among them, Architects are more receptive towards digital technology adoption. The above conclusion is beneficial for the local construction community and authority towards strategical charting and policies formulations of the industry to embrace the benefits of digital economy which is already here.